Transcriptome analysis reveals early activation of MAPK pathways involved in the resistance of Setaria italica against Pyricularia setariae - Feng, Shang; Liu, Jia; Han, Xinpeng; Liu, Tingting; Wang, Saiya; Xin, Shaoshuai; Hao, Zhimin; Li, Zhiyong (Frontiers in Plant Science, 2025)
Millet (Setaria italica) is an important food crop in China, and its yield and quality are often severely threatened by foxtail millet blast (the pathogen is Pyricularia setariae). Currently, the molecular mechanism of millet’s resistance to P. setariae, especially the key regulatory links of the early signal transduction pathway, is still poorly understood. The mitogen-activated protein kinase (MAPK) signaling pathway plays a conserved and crucial role in plant immunity, rapidly activating downstream defense genes to respond to pathogen invasion. However, the specific function of this pathway in the interaction between S. italica and P. setariae and its contribution to disease resistance remain unclear. To clarify the role of the MAPK pathway in millet’s disease resistance process, this study selected the high-resistance variety ZGB and the high-susceptibility variety JG19, and used RNA-seq technology to systematically analyze the dynamic changes in the leaf transcriptome after inoculation with P. setariae. KEGG pathway analysis showed that in the resistant variety, genes related to photosynthesis and ribosomes were downregulated in the early stage of infection and then rapidly upregulated, demonstrating a strong self-repairing ability; while in the susceptible variety, these genes were continuously downregulated, resulting in severe damage to physiological functions. Further studies have shown that this regulatory process may be closely related to the MAPK signaling pathway. This study focuses on expression differences of MAPK pathways and their downstream transcription factors in resistant and susceptible varieties aiming to reveal regulatory roles of this pathway in early immune responses of millet while providing theoretical basis as well as genetic resources for analyzing mechanisms underlying disease resistance.